ANALYSIS OF UNDERSTANDING OF STORYTELLING IN MARKETING FOR LAWEYAN BATIK ENTREPRENEURS - Ahmada Auliya Rahman; Syahara Dina Amalia; Agshala Akbar Priananda; Agrefo Satria Khrisnahadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Kampoeng Batik Laweyan is an educational tourist destination as well as a shopping tour in Surakarta. Batik entrepreneur is a major player in the batik industry. Industrial areas and batik tourism can be enhanced with various marketing strategies, one of which is by utilizing storytelling marketing. Previous research has proven that the use of storytelling marketing can have a positive impact in increasing brand value, increasing customer loyalty and even making customers willing to pay more to get the product. This study aims to reveal the understanding of storytelling in marketing activities for Laweyan batik entrepreneurs. This study uses qualitative methods and a descriptive approach with data from interviews with Laweyan batik entrepreneurs regarding their understanding of marketing storytelling and marketing documents. Interview results were validated by observation as a form of triangulation in this study. Research subjects were selected by purposive sampling technique with a certain mix. The results of this study found that understanding of marketing strategies by utilizing storytelling marketing is still lacking, because Laweyan batik entrepreneurs are still focused on increasing product selling points, they do not explain the ability to retain customers and also attract potential customers.